Surgical Treatment of Multiple Large Tuberous and Tendinous Xanthoma Secondary to Familial Hypercholesterolaemia: A Case Report - Guan H; Zhang G; Li Q; Lian J; Dong Z; Zhu L; Xiao K (Dove Medical Press, 2024)
Haonan Guan,* Guoyou Zhang,* Qiqi Li, Jie Lian, Zhaoyang Dong, Lian Zhu, Kaiyan Xiao Department of Plastic and Reconstructive Surgery, Shanghai Ninth People's Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Kaiyan Xiao, Department of Plastic and Reconstructive Surgery, Shanghai Ninth People's Hospital, Shanghai Jiaotong University School of Medicine, 639 Zhizaoju Road, Shanghai, People's Republic of China, Tel +86 021 23271699, Fax +86 021 63136856, Email xky7026@163.comAbstract: Xanthomas are well-circumscribed skin lesions that are commonly seen in patients with familial hypercholesterolemia (FH). The aim of this report is to present a rare case of multiple large tuberous and tendinous xanthomas. A 17-year-old female patient in this report presented with multiple asymptomatic and papulo-nodular masses in both sides of palms, elbows, buttocks, knees, and Achilles tendons. Surgical removal of the masses was carried out in combination with lipid-lowering therapy. A following up of 3 months showed all wounds were healing well, and no recurrence of masses was observed. Therefore, for patients with xanthomas related with familial hypercholesterolaemia, lipid-lowering therapy has reportedly reduced the size of masses, but surgical treatment may be essential for large xanthomas caused pain or limitation of daily activities.Keywords: soft-tissue tumors, lipoprotein, atorvastatin, foam cells, lipid-lowering therapy